2013
DOI: 10.4236/ojpm.2013.32023
|View full text |Cite
|
Sign up to set email alerts
|

Utility of nelson’s modified card sorting test in patients with alzheimer’s disease or vascular dementia

Abstract: Aim: In this study we used the Nelson's Modified Card Sorting Test (MCST) to find the differences between Alzheimer's disease (AD) group/Vascular dementia (VD) group and a normal control group (non-dementia and non-AD), and to identify the commonality between the MCST and dementia patients. Patients and Methods:The MCST was administered to 32 AD patients, 18 vascular dementia patients, and 38 controls. The relationship between the MCST performance and demographic characteristics was evaluated. Results: There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…Our findings, in conjunction with findings regarding the sensitivity of the WCST in detecting AD (Bondi et al, 1993;Chao et …”
Section: Neuropsychologysupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings, in conjunction with findings regarding the sensitivity of the WCST in detecting AD (Bondi et al, 1993;Chao et …”
Section: Neuropsychologysupporting
confidence: 84%
“…14 Chao et al, 2013;Nagahama et al, 2003), and extended them to show its sensitivity to risk for AD in cognitively intact elders. The results also complement and extend a recent report showing the sensitivity of a battery of executive measures to FH in cognitively intact elders (Donix et al, 2012).…”
Section: Neuropsychologymentioning
confidence: 98%
“…Furthermore, both from the neuropsychological context and the research perspective, an increasing need has been observed to have shorter protocols that facilitate the task, since a protocol that is too long can consume resources that in some cases are very limited. 31 By way of conclusion, we can say that our findings indicate that the use of only 1 deck (the WCST-64) provides the same information in patients with AD as the use of both decks (the full version), as we found the 2 decks to be equivalent for all the items with the exception of "number of hits," which decreases with the second deck, possibly as a result of the long duration of the test. 13 It is also important to underscore the sensitivity of the test, since it found significant differences between the CG and the experimental group for all the test items.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, both from the neuropsychological context and the research perspective, an increasing need has been observed to have shorter protocols that facilitate the task, since a protocol that is too long can consume resources that in some cases are very limited. 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation